Remote ultrasonic imaging of a wire arc additive manufactured Ti-6AI-4V component using laser induced phased array - Lukacs, Peter; Davis, Geo; Stratoudaki, Theodosia; Williams, Stewart; MacLeod, Charles N.; Gachagan, Anthony (IEEE, 2021)
Additive manufacturing (AM) has been revolutionizing the manufacturing industry due to its ability to significantly reduce waste and produce components with intricate shapes. Laser Ultrasonics (LU) is a non-contact and couplant free method to generate and detect ultrasound. LU can accommodate complex component shapes; thus, it has the potential to provide a reliable in-process inspection method for AM components. In recent years the development of Laser Induced Phased Arrays (LIPAs) helped overcome the inherently low signal amplitudes of LU at the non-destructive, thermoelastic regime. In this paper, the Full Matrix Capture data acquisition method is used and a LIPA of 68 elements is synthesized in post processing. The Total Focusing Method imaging algorithm is applied for ultrasonic imaging. The technique is demonstrated on a highly scattering titanium alloy Wire Arc Additive Manufactured (WAAM) component producing high quality ultrasonic images, accurately imaging defects at depths up to 10mm below the inspection surface
Keywords: remote sensing; additive manufacturing; ultrasonic imaging; laser ultrasonics